Study the State of Hemodynamics and Ophthalmotonus When Using Propofol and Fentanyl in Ophthalmic Surgery - Bektemirova Norbuvi Tukhtaevna (Genius Journals, 2023)
Anesthesia in ophthalmology is an urgent problem of modern medicine, which is due to the specifics of intraocular operations. This is, first of all, a state of ophthalmotonus, which is influenced by both local and general anesthesia. If the volume of blood inside the eye increases, the intraocular pressure (IOP) also increases. An increase in venous pressure leads to an increase in IOP due to a decrease in the outflow of aqueous humor and an increase in blood volume in the choroid. Fluctuations in CVP, BP, PaCO2 and PaO2 affect IOP.
Keywords: Propofol; fentanyl; IOP; ADsyst